A treatise on the decorative part of civil architecture - Sir William Chambers... (Editeur non renseigne, 1791)
Notice de démonstration issue d Open Library pour la thematique 'architecture'. Titre: 'A treatise on the decorative part of civil architecture'. Auteur: Sir William Chambers | Joseph Gwilt. Premiere publication: 1791.
Droits : Métadonnées bibliographiques issues dOpen Library
Keywords: architecture; patrimoine; Patrimoine bâti; Patrimoine